A review of current management of vasculo-Behcet's. Issue 1 (January 2018) - Merashli, Mira; Eid, Rozana El; Uthman, Imad
Abstract : Purpose of review: To give an overview of recently published articles about the management of vasculo-Behcet's with particular emphasis on anticoagulation. Recent findings: Biologic agents are emerging as a potential therapeutic option in refractory vasculo-Behcet with a good safety profile. Evidence further shows that following nonpulmonary aneurysm repair, there is a reduced risk of recurrent aneurysmal formation at the operative site in patients treated with immunosuppressants in addition to their surgery, than those undergoing surgical intervention alone. Summary: Behcet disease patients are at risk of developing multiple vascular complications including thrombosis and aneurysms. Treatment should focus on reducing inflammation; and the role of anticoagulation is still debatable.